A Sequência de Fibonacci e algumas de suas aplicações - Borges, Fábio Pereira (2015)
In this work is a sequence generated by a problem called ‘problem of rabbits’ Fibonacci, which is the Fibonacci sequence (1.1, 2, 3, 5, ...). Specifically, it is an analysis of how such sequence is being addressed in some textbooks of high school, a study of some properties and certain appearances in nature. In addition, it is proposed that some activities that can be worked in conjunction with other content covered in high school.